Behavior of dissolved radiocesium in river water in a forested watershed in Fukushima Prefecture. Issue 10 (12th October 2016) - Tsuji, H.; Nishikiori, T.; Yasutaka, T.; Watanabe, M.; Ito, S.; Hayashi, S.
Abstract: Dissolved radiocesium concentrations in river water in a high‐dose‐rate forest watershed in Fukushima Prefecture were investigated under base flow and storm flow conditions. Under base flow conditions, dissolved 137 Cs concentrations in water (Bq/L) were relatively high in summer, and these levels were higher than particulate 137 Cs concentrations (Bq/L). Under storm flow, particulate 137 Cs concentration became dominant as the suspended solid concentration increased. Throughout the monitoring period, dissolved 137 Cs concentrations in water (Bq/L) were higher under storm flow than base flow conditions and were positively correlated with runoff intensity. Factors influencing changes in dissolved 137 Cs concentrations were investigated by measuring the 137 Cs concentration of suspended solid (Bq/kg) and dissolved 137 Cs of unsaturated soil water, throughfall, and rainfall, together with other main solute concentrations. The 137 Cs concentration per unit weight of suspended solids in river water was not strongly correlated with runoff intensity. Additionally, dissolved 137 Cs concentrations of soil water, groundwater, and rainfall were not detected, while higher dissolved 137 Cs concentrations were detected in throughfall than river water. K + concentrations were higher under storm flow than base flow, and dissolved organic carbon increased toward the peak flow rate. These findings suggested that one main factor influencing generation of dissolved 137 Cs in the river water was leaching from organic material in flooded areas. However, further investigation is needed to clarify the dominant source of dissolved 137 Cs in river water. Key Points: Dissolved 137 Cs concentration in forest river water peaked in summer under base flow Dissolved 137 Cs concentrations became higher under storm flow relative to base flow The 137 Cs desorbed from litter might be an influential source of dissolved 137 Cs in river water